Colorectal cancer–associated T cell receptor repertoire abnormalities are linked to gut microbiome shifts and somatic cell mutations - Yuan Cao; Jifeng Wang; Weiliang Hou; Yanqiang Ding; Yefei Zhu; Jiayi Zheng; Qiongyi Huang; Zhan Cao; Ruting Xie; Qing Wei; Huanlong Qin (Gut Microbes, 2023)
ABSTRACTAs with many diseases, tumor formation in colorectal cancer (CRC) is multifactorial and involves immune, environmental factors and various genetics that contribute to disease development. Accumulating evidence suggests that the gut microbiome is linked to the occurrence and development of CRC, and these microorganisms are important for immune maturation. However, a systematic perspective integrating microbial profiling, T cell receptor (TCR) and somatic mutations in humans with CRC is lacking. Here, we report distinct features of the expressed TCRβ repertoires in the peripheral blood of and CRC patients (n = 107) and healthy donors (n = 30). CRC patients have elevated numbers of large TCRβ clones and they have very low TCR diversity. The metagenomic sequencing data showed that the relative abundance of Fusobacterium nucleatum (F. nucleatum), Escherichia coli and Dasheen mosaic virus were elevated consistently in CRC patients (n = 97) compared to HC individuals (n = 30). The abundance of Faecalibacterium prausnitzii and Roseburia intestinalis was reduced in CRC (n = 97) compared to HC (n = 30). The correlation between somatic mutations of target genes (16 genes, n = 79) and TCR clonality and microbial biomarkers in CRC had been investigated. Importantly, we constructed a random forest classifier (contains 15 features) based on microbiome and TCR repertoires, which can be used as a clinical detection method to screen patients for CRC. We also analysis of F. nucleatum-specific TCR repertoire characteristics. Collectively, our large-cohort multi-omics data aimed to identify novel biomarkers to inform clinical decision-making in the detection and diagnosis of CRC, which is of possible etiological and diagnostic significance.